Ecological drivers of soil microbial diversity and soil biological networks in the Southern Hemisphere - Delgado-Baquerizo, Manuel; Reith Frank; Dennis Paul G.; Hamonts Kelly; Powell Jeff R.; Young Andrew; Singh Brajesh K.; Bissett Andrew (Ecology, 2018)
Ecological drivers of soil microbial diversity and soil biological networks in the Southern Hemisphere. Published in Ecology